Clergy Burnout: A Self Psychology and Systems Perspective - Olsen, David C. (The Journal of pastoral care, 1991)
Examines the underlying causes of clergy burnout and suggests that burnout may be an interaction of three factors: a narcissistic personality style on the part of clergy craving admiration and appreciation the demands of parish life, and the developmental needs of the clergy's own family. Attempts to understand the interaction of these three factors from the vantage points of self psychology and systems theory. Uses Kohut's description of narcissism to show how a narcissistic style interacts with issues in both the family system and in the congregational system of the pastor. Offers suggestions regarding prevention, including group work.